THE DAYS OF ABANDONMENT - Ferrante, Elena; Goldstein, Ann, 1949- (London : Europa Editions, 2021)
Rarely have the foundations upon which our ideas of motherhood and womanhood rest been so candidly questioned. This compelling novel tells the story of one woman's headlong descent into what she calls an absence of sense after being abandoned by her husband. Olga's days of abandonment become a desperate, dangerous freefall into the darkest places of the soul as she roams the empty streets of a city that she has never learned to love. When she finds herself trapped inside the four walls of her apartment in the middle of a summer heat wave, Olga is forced to confront her ghosts, the potential loss of her own identity, and the possibility that life may never return to normal again.
Keywords: Depressed persons -- Fiction; Housewives -- Fiction; Loneliness -- Fiction